Vegetative adaptability of the Peruvian palm Astrocaryum perangustatum to deforestation - Aponte, Héctor (2011)
Variation in vegetative morphology of the palm Astrocaryum perangustatum as a response to deforestation was evaluated from a sample of 60 individuals (30 in forest and 30 in pasture) located in the Pozuzo region of Pasco, Peru. Several parameters are significantly different between palms growing in the forest understory and those growing in pasture. These include: number of leaves in the crown, length of the stem, of the leaves, length and width of proximal pinnae, width of medial pinnae, size of spines in adult palms, and number and length of leaves in seedlings. Variation in vegetative morphology of Astrocaryum perangustatum between forest and pasture is discussed in relation to environmental conditions. Morphological variability in the Pozuzo region is compared with that obtained from herbarium vouchers collected throughout the distribution area of the species.